Nitrogen fixating ability of mungbean genotypes under different levels of nitrogen application (Bangladesh Journal of Agricultural Research, 2016)
A pot culture experiment was conducted at the Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Gazipur during kharif II, 2012 to evaluate the nodulation, biological nitrogen fixation and yield potential of genotypes of mungbean under varying levels of N application. There were 10 mungbean genotypes viz. IPSA 12, GK 27, IPSA 3, IPSA 5, ACC12890055, GK 63, ACC12890053, BU mug 4, BARI Mung 6 and Binamoog 5, each genotype treated with six levels of N (0, 20, 40, 60, 80 and 100 kg N ha-1) . Among the genotypes, the IPSA 12 at 40 kg N ha-1 produced the maximum number of nodules (14.54 plant-1) as well as the highest nitrogen fixation (2.684 mmol C2H4). This resulted in the highest seed yield (14.22 g plant-1). The genotype ACC12890053 recorded the lowest nodulation (6 plant-1), nitrogen fixation (1.134) and seed yield (7.33 g plant-1).Bangladesh J. Agril. Res. 41(1): 163-171, March 2016